Influence of different host blood meal sources on the reproductive outcomes in Anopheles gambiae: Enhancing fecundity in a mass rearing environment - Celestine N. Wekesa; Maxwell G. Machani; Nabie M. Bayoh; Z. Ngalo Otieno-Ayayo; Maurice V. Ombok; Eric O. Ochomo (PLoS ONE, 2025)
Identification of blood sources for maximum production of Anopheles mosquitoes is an important consideration for colony maintenance which involves mass rearing. High feeding rates, eggs production, hatching rates, larval, pupal, and adult survivorship are essential parameters to consider when selecting a blood host for mass production of An. gambiae. Here, we investigated the feeding success, reproduction performance and survivorship of An. gambiae when fed on blood from five different hosts: cow, goat, sheep, pig, and chicken compared to human blood. There was significant variations in feeding success (F5, 18 =  35.34, p < .001), egg laying (F 5,18 = 12.57, p < .001), number of eggs laid (F5, 18 = 34.23 p < .001), egg hatchability (F 5, 114 =  37.63, p < .001), pupation time (F 5,18 =  5.532763, p = 0.0029) and pupation rates (F 5,18 =  8.26, p < .001). Feeding success was highest in human blood meal (Mean = 125.25 ±  3.86), followed by pig blood meal (Mean = 123 ±  7.93), with no statistically significant difference between the two. The highest proportion of females that laid eggs were those fed on human blood (Mean =  36.50 ±  2.08) followed by those fed on chicken blood meals (Mean =  27.50 ±  5.44) and then pig blood meal (Mean =  26.25 ±  2.87). The mean number of eggs laid per mosquito was highest among those fed on human blood meal (111.65 ±  5.74) followed by those fed on pig blood meal (100.46 ±  6.36). The most favorable outcomes were observed with human blood for hatchability (88.35 ±  5.61%), pig blood for pupation percentage (Mean =  83.50 ±  4.79), and goat blood for pupation time (9.79 ±  0.41 days). Larval survival rates did not significantly differ among blood meal sources (F 5,92 =  0.13, p = 0.985). Nonetheless, the highest survival rate was observed with pig blood meal (Mean =  0.57 ±  0.11). Survival rates of adult F1 varied significantly across blood meals (F 6,346 = 133.19, p < .001), with human blood meal showing the highest survival rate (Mean =  0.73 ±  0.04). However, pig blood meal (56 days) demonstrated the longest survival period, close to human blood meal (57 days). This study revealed pig blood as an excellent alternative to human blood meal for the mass production of An. gambiae.